Lexical complexity in the writings of Iraqi, English L2, and English L1 writers / Ali Alsahlanee and Paramaswari Jaganathan - Alsahlanee, Ali; Jaganathan, Paramaswari (Universiti Teknologi MARA, 2022)
Lexical complexity is an essential construct in L2 writing studies. It has been widely utilized to evaluate writing quality and writers’ proficiency. Measures of lexical complexity were considered reliable indicators of writing quality. The more lexical complexity measures score, the more high-quality rating writing. Since the measures of lexical complexity are correlated with writing quality, investigating lexical complexity in the writing of Iraqi writers, and comparing it with the writing of other groups of writers, such as English L2 and L1 writers, intends to describe the current situation of Iraqi writers in terms of using the English language for research publication purposes. This study utilizes the corpus-based method to analyze and compare lexical complexity in the texts of linguistics research articles RAs written by Iraqi, English L2, and English L1 writers and published in international journals indexed in the Scopus database. Eight lexical complexity measures were calculated by using Lexical Complexity Analyzer LCA. The findings revealed a significant difference between Iraqi writers and other groups of writers. There is a gap between the writings of Iraqi writers and English L2 and L1 writers in terms of using complex lexical items. Iraqi writers utilized the lowest amount of lexical complexity in their texts of linguistics RAs.